Pemberdayaan Kelompok Pembudidaya Ikan Hias di Kawasan Minapolitan Desa Cibadung, Kecamatan Gunung Sindur, Kabupaten Bogor, Jawa Barat - Chikita Lestari Saputriningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Cibadung Village, Gunung Sindur District is one of the centers for ornamental fish cultivation in the Minapolitan Area, Bogor Regency, West Java Province. In ornamental fish farming activities, there are obstacles, namely the lack of access to capital for business development. Meanwhile, the market demand for ornamental fish from Bogor Regency is very high. This empowerment activity, especially assistance on access to capital, was carried out from January 2019 to December 2020 with the group of cultivators who were assisted, namely the Viece Key ornamental fish cultivator group, Cibadung Village in the Minapolitan area of ​​Gunung Sindur, Bogor. The purpose of this activity is technical assistance for cultivation, group strengthening and access to business capital. The results of the activity show an increase in the technical ability of cultivation with indicators of survival rates from 70% to 90%; production before being accompanied by 1000 - 2000 tail/month 1 type of commodity, after being assisted to 4000 - 7000 tail/month; group strengthening from beginner to intermediate class; and from never having access to capital to being able to access business capital worth Rp 30,000,000, and Rp 5,000,000 has been returned; and the rest will receive a one-year extended return by the instructions of the President of the Republic of Indonesia during the COVID-19 pandemic. The R/C ratio from the business analysis is 3 which states that this business is feasible to develop.